MARKETING GUIDELINES FOR THE SALE OF PRODUCTS OF AGRIBUSINESS ENTERPRISES IN THE CONDITIONS OF DIGITALIZATION - KASHULSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Developing agrarian businesses, filling the domestic market with the necessary agricultural sector products, ensuring food security, and forming export potential are essential tasks for agricultural enterprises. The market situation of agrarian businesses is formed so that the problems of selling agricultural products occupy a significant place. Under modern conditions, the issues of applying innovative technologies and using the latest methods of promoting products to consumers and their sales are particularly relevant. For such purposes, digitalization and the application of digital technologies are used, which serve as a powerful marketing tool for effective business development, promotion, and sales of products. The purpose of the publication is to study the essence and features of the marketing principles for selling products of agribusiness enterprises using digital tools and technologies in modern realities. The article examines issues regarding the features, development, and application of digital marketing tools for promoting and selling agribusiness products. The essence of product sales is determined, and it is investigated that the product sales system includes product promotion channels, sales planning, marketing support for sales, information support, sales control, and logistics. Aspects of marketing policy that affect the effectiveness of marketing at the enterprise are identified. The features of agricultural marketing and the areas it includes are studied. Attention is paid to the processes of applying digital marketing tools that can be implemented in the marketing of agribusiness enterprises' products and contribute to rural areas' development. Problematic aspects of introducing digital technologies into the marketing, promoting, and selling agricultural products are studied.Digitalization of marketing is a promising direction that can change the face of agribusiness and rural areas. Digital marketing opens up opportunities for small and medium-sized enterprises, farmers, and entrepreneurs, allowing them to enter broader markets, improve their products and services, and improve the population's quality of life. Optimization of the process of implementing digital technologies in the marketing of agricultural products requires an integrated approach that takes into account both technical and socio-economic aspects. Integrating digital technologies into marketing opens up new horizons for development that can bring significant benefits to rural entrepreneurs and society as a whole.
Keywords: digital tools and technologies; sales; product promotion; agribusiness; agricultural marketing